Boron carbide dispersed epoxy composites for gamma radiation shielding applications. (November 2022) - S, Vignesh; Jappes JT, Winowlin; S, Nagaveena; Sharma R, Krishna; Khan M, Adam
Abstract: The present article deals with the preparation of B4 C dispersed epoxy composites for irradiation shielding applications. The samples of five different compositions were made through molding and curing route and were subjected to thermal characterization and irradiation attenuation studies. The thermal stability of the samples increased due to the intrinsic conductivity of the filler particles whereas the shielding performance of samples increased with an increased addition of B4 C at lower energies due to photoelectric absorption than that at higher energies, which makes the as-prepared sample suitable for low dose shielding applications. Highlights: Boron carbide reinforced epoxy composites were made through molding and curing route. Thermal stability and gamma radiation shielding studies were done. Radiation shielding efficiency improved with increased addition of boron carbide.